Long-term treatment results of multilevel cervical spine stenosis with the method of bilateral osteoplasticic decompression laminoplasty and simultaneous foraminotomy - Albert A. Sufianov; Aleksandr V. Burtsev; David N. Nabiev; Asiyat Sh. Magomedova; Rinat A. Sufianov; Maria T. Karsanova; Vladislav V. Piterov (Гений oртопедии, 2023)
Introduction Stenosis of the cervical spine can lead to serious complications resulting from spinal cord dysfunction. There are different methods of posterior decompression of the spinal canal. The method of choice for surgical treatment of cervical stenosis is laminoplasty. Purpose Analysis of long-term (from 2 to 5 years) results of clinical outcomes after bilateral decompression laminoplasty and simultaneous foraminotomy Materials and methods Study design: case series (27 patients); a single center retro/prospective study. Patients who were treated at the Federal Center for Neurosurgery in Tyumen were examined. In the pre- and postoperative periods, the clinical condition of patients was assessed using questionnaires and scales JOA, VAS, Nurick. The stenosis severity was objectively assessed using a standard closed polygon measuring instrument. The cross-sectional area of the dural sac and the average linear dimensions were measured according to neuroimaging data. Results In the late postoperative period, patients had positive dynamics in pain relief, improvement in motor functions, and partial recovery of sensory disorders. There was a slight increase in the average cross-sectional area of the dural sac measured at the follow-up. Discussion The method of bilateral osteoplastic laminoplasty is one of the surgical treatment options and allows full visualizing of the neurovascular structures, as well as safe performance of hemostasis and foraminotomy at the levels of interest. Conclusion Thus, the effectiveness of this technique was shown by this study.